2013
DOI: 10.3748/wjg.v19.i46.8515
|View full text |Cite
|
Sign up to set email alerts
|

Lymph node staging in colorectal cancer: Old controversies and recent advances

Abstract: Outcome prediction based on tumor stage reflected by the American Joint Committee on Cancer (AJCC)/Union for International Cancer Control (UICC) tumor node metastasis (TNM) system is currently regarded as the strongest prognostic parameter for patients with colorectal cancer. For affected patients, the indication for adjuvant therapy is mainly guided by the presence of regional lymph node metastasis. In addition to the extent of surgical lymph node removal and the thoroughness of the pathologist in dissecting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
75
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(81 citation statements)
references
References 68 publications
5
75
0
1
Order By: Relevance
“…Inappropriate activation or altered expression of ECHS1 is involved in several regulatory processes associated with the occurrence and progression of tumors. Elevated expression of the ECHS1 protein has been detected in several malignant tumors, including liver, colorectal, breast, bladder and prostate cancers (10). In this study, we observed a significant increase in the expression of the ECHS1 protein in CRC tissues compared to that in proximal non-cancerous colorectal tissues.…”
Section: Discussionsupporting
confidence: 62%
“…Inappropriate activation or altered expression of ECHS1 is involved in several regulatory processes associated with the occurrence and progression of tumors. Elevated expression of the ECHS1 protein has been detected in several malignant tumors, including liver, colorectal, breast, bladder and prostate cancers (10). In this study, we observed a significant increase in the expression of the ECHS1 protein in CRC tissues compared to that in proximal non-cancerous colorectal tissues.…”
Section: Discussionsupporting
confidence: 62%
“…1 Following surgical treatment, the presence of lymph node metastasis has been associated with a poor prognosis, as has inadequate lymph node retrieval. 25 However, the use of adjuvant chemotherapy, particularly oxaliplatin, has been demonstrated to provide a significant survival benefit for patients with lymph node disease. 68 …”
mentioning
confidence: 99%
“…Colorectal carcinomas with lymph node metastases (LNM) differ in many aspects from those that do not present nodal dissemination. The former show worse prognosis, a higher recurrence rate, and shorter overall and disease-free survival [4,5]. Additionally, application of adjuvant systemic therapy also depends on the lymph node involvement [6].…”
Section: Introductionmentioning
confidence: 99%